Diagnóstico de la existencia y uso de la maquinaria agrícola en el cantón Puebloviejo, Provincia de Los Ríos en el año 2023 - Valenzuela Velasco, Genesis Jacsely (2023)
This present work is based on the investigation of the usage and existence of agricultural machinery in Puebloviejo Canton, Los Ríos Province, through a descriptive, non-experimental research approach, utilizing survey methodology conducted in the canton's parishes. The utilization of agricultural machinery in short-cycle crops aims to enhance agricultural efficiency, productivity, and sustainability. Short-cycle crops play a pivotal role in ensuring food security and bolstering the agricultural economy, as they enable rapid harvesting within a relatively short timeframe. A detailed study of agricultural machinery usage in short-cycle crops will be undertaken, emphasizing its significance for the agricultural sector. Additionally, an evaluation of the environmental and economic impact of machinery usage will be conducted. The information gathered through surveys, interviews, and direct observations will yield data on the types of available agricultural machinery, their condition, usage levels, areas of application, and the limitations that farmers face in their utilization.